HDAC11 regulates expression of C/EBPβ and immunosuppressive molecules in myeloid-derived suppressor cells. Issue 5 (18th April 2021) - Chen, Jie; Cheng, Fengdong; Sahakian, Eva; Powers, John; Wang, Zi; Tao, Jianguo; Seto, Edward; Pinilla-Ibarz, Javier; Sotomayor, Eduardo M
Abstract: Myeloid-derived suppressor cells (MDSCs) constitute a heterogeneous population of immature myeloid cells derived from bone marrow and negatively regulate both innate and adaptive immunity in the tumor microenvironment. Previously we have demonstrated that MDSCs lacking histone deacetylase 11 (HDAC11) displayed an increased suppressive activity against CD8 + T-cells. However, the mechanisms of HDAC11 that contribute to the suppressive function of MDSCs remain unclear. Here, we show that arginase activity and NO production is significantly higher in HDAC11 knockout MDSCs when compared with wild-type (WT) controls. In the absence of HDAC11, elevated arginase level and enzymatic activity were observed preferentially in the tumor-infiltrated granulocytic MDSCs, whereas iNOS expression and NO production were increased in the tumor-infiltrated monocytic MDSCs. Of note and for the first time, we demonstrated an association between the elevated expression of immunosuppressive molecules with up-regulation of the transcription factor C/EBPβ in MDSCs lacking HDAC11. Interestingly, the highest expression of C/EBPβ was observed among CD11b + Gr-1 + MDSCs isolated from tumor-bearing mice. The additional demonstration that HDAC11 is recruited to the promoter region of C/EBPβ in WT MDSCs suggests a novel molecular mechanism by which HDAC11 influence the expression of immunosuppressive molecules in MDSCs through regulation of C/EBPβ gene expression. Graphical Abstract: HDAC11 negatively regulates MDSCs function through down-regulation of C/EBPβ.